The Concept of Naskh in the Perspective of Ali As-Shabuni (Study of Rawāi’ Al-Bayān Tafsīr Āyāṭ Al-Aḥkām min Al-Qur’ān) - Abdillah Amiril Adawy (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
The concept of naskh in the disciplines of the Qur’an and useful fiqh is understood as the cancellation of the previous Sharia law, which is replaced by a new law, as part of an adjustment to the needs and dynamics of the development of Muslims at the time of the Prophet Muhammad. This concept has generated polemics among scholars. Some allow it, and those who reject it. Through the descriptive-analytical method and reviewing various related literature references, the author attempts to present the views of scholars and specifically explore the views of Ali As-Shabuni, a contemporary scholar from Aleppo, Syria, in his work Rawāi’ Al-Bayān Tafsīr Āyāṭ Al-Aḥkām min Al-Qur’ān related to the dynamics of naskh. The results of this study show that Ali As-Shabuni’s view of naskh is contrary to the views of the majority of scholars on its permissibility. However, in his book, he provides a separate review of the wisdom behind the ordinance of naskh. He also gives a fairly detailed explanation to refute the views that reject the application of the concept of naskh in the Qur'an and Sunnah. He concludes that naskh has great significance in the formation of dynamic sharia law, as well as a gift in the form of the process of tadarruj al-hukm given by Allah to His servants.